Intra-Abdominal Hypertension and Abdominal Compartment Syndrome in Association with Ruptured Abdominal Aortic Aneurysm in the Endovascular Era: Vigilance Remains Critical - Matthew C. Bozeman; Charles B. Ross (Critical Care Research and Practice)
Intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS) are common complications of ruptured abdominal aortoiliac aneurysms (rAAAs) and other abdominal vascular catastrophes even in the age of endovascular therapy. Morbidity and mortality due to systemic inflammatory response syndrome (SIRS) and multiple organ failure (MOF) are significant. Recognition and management of IAH are key critical care measures which may decrease morbidity and improve survival in these vascular patients. Two strategies have been utilized: expectant management with prompt decompressive laparotomy upon diagnosis of threshold levels of IAH versus prophylactic, delayed abdominal closure based upon clinical parameters at the time of initial repair. Competent management of the abdominal wound with preservation of abdominal domain is also an important component of the care of these patients. In this review, we describe published experience with IAH and ACS complicating abdominal vascular catastrophes, experience with ACS complicating endovascular repair of rAAAs, and techniques for management of the abdominal wound. Vigilance and appropriate management of IAH and ACS remains critically important in decreasing morbidity and optimizing survival following catastrophic intra-abdominal vascular events.